Perspektif Siswa terhadap Peran Moderasi Beragama dalam Membentuk Siswa Moderat di MTsN 16 Jombang - Susanti, Siti; Huda, Saihul Atho Alaul; Waslah, Waslah (ALSYS, 2025)
This study is motivated by the importance of instilling religious moderation values within educational environments, particularly at MTsN 16 Jombang, which is situated in a diverse community. The objective of the research is to explore the process of embedding religious moderation values, the role of teachers and the school environment in supporting this effort, as well as students’ perspectives on the importance of adopting a moderate attitude in daily life. The study also identifies the challenges faced in shaping tolerant students capable of living harmoniously amidst diversity. Using a qualitative approach with observation, interviews, and documentation techniques, the study finds that MTsN 16 Jombang promotes religious moderation through regular religious activities, teacher role modeling, and instructional practices that emphasize tolerance and inclusivity. Students demonstrate understanding and a positive attitude toward religious moderation values. However, the school faces challenges such as its remote geographical location and external influences that conflict with the principles of moderation. The study concludes that the implementation of religious moderation at MTsN 16 Jombang is effectively carried out through integrated strategies embedded in school life, with teachers and a supportive environment playing crucial roles in fostering inclusive character. The findings imply that religious moderation education must continue to be strengthened as part of broader efforts to build a tolerant and peaceful society.